Financial Performance Analysis of Nirlaba Organization (Case Study on the National Zakat Amil Agency of Lumajang Regency 2018 - 2022) - Mi’rotin Ivanasari; Endro Sugiartono; Dessy Putri Andini; Berlina Yudha Pratiwi (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the financial performance of the National Amil Zakat Agency of Lumajang Regency in 2018 to 2022. In analyzing financial performance in this study using activity ratios, efficiency ratios, amil fund ratios, liquidity ratios, and growth ratios in accordance with guidelines issued by the National Amil Zakat Agency's strategic study center. This research uses a qualitative descriptive approach. The types and sources of data used are secondary data in the form of financial reports of BAZNAS Lumajang Regency in 2018 - 2022 with data collection methods, namely documentation. The results showed that the average activity ratio of BAZNAS Lumajang Regency was effective, and showed good results in terms of collecting and distributing Zakat, Infaq, Sadaqah (ZIS) funds. Based on the average efficiency ratio, it shows efficient results even though the ratio of operational costs to total amil rights is still inefficient. Based on the ratio of amil funds good results were obtained. Based on the average results of the liquidity ratio is not good because it indicates the obligation to distribute ZIS funds that have not been realized. Based on the ratio of collection growth the results obtained also show not good.